PENERAPAN METODE PROTOYPE PADA PERANCANGAN E-BUSINESS AIR MINUM ISI ULANG BAROKAH : Prototype Method, E-Business, Refill Drinking Water - Kurniawan, Tomi; Rahmawati, Noni; Ramadani, Rio; -, Suroto; Syah , Thamrin (JURNAL AKADEMIKA, 2025)
The rapid advancement of technology has influenced business processes, including refill drinking water businesses. This study applies the Prototype Method in designing an e-business system for "Barokah" refill drinking water. The Prototype Method allows for iterative development based on user feedback, ensuring a system that meets customer needs effectively. The designed e-business system includes online ordering, transaction management, and customer service features to improve efficiency and accessibility. Through continuous evaluation and refinement, the prototype helps identify potential issues early, reducing risks in system development. The results indicate that the prototype-based approach enhances user satisfaction and business operations, making the service more efficient and competitive. This study demonstrates that implementing the Prototype Method in e-business design can optimize digital transformation in small businesses.